2019
DOI: 10.1177/0193945919847937
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing a Mobile Health Intervention to Manage Hypertension in an Underserved Community

Abstract: This 6-month pilot randomized controlled trial examined the effectiveness of a Mobile Health (mHealth) intervention for hypertension self-monitoring and management in an underserved urban community. The four health outcomes measured included changes in systolic and diastolic blood pressure (BP), BP monitoring adherence, perceived medication adherence self-efficacy, and health-related quality of life. Thirty participants were randomly assigned to the mHealth group or a standard follow-up group; 25 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
128
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(131 citation statements)
references
References 35 publications
2
128
0
1
Order By: Relevance
“…Moreover, in this study, the greater pooled improvements reached significance for SBP. Our result was consistent with those of the studies by Zha, 46 Haas et al 47 and Nolan et al, 48 which illustrated that eHealth interventions effectively improved the level of SBP. This effect might be because eHealth interventions could be more flexibly fitted to MetS patients' lives and promote greater adherence to the lifestyle programme.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in this study, the greater pooled improvements reached significance for SBP. Our result was consistent with those of the studies by Zha, 46 Haas et al 47 and Nolan et al, 48 which illustrated that eHealth interventions effectively improved the level of SBP. This effect might be because eHealth interventions could be more flexibly fitted to MetS patients' lives and promote greater adherence to the lifestyle programme.…”
Section: Discussionsupporting
confidence: 93%
“…It causes chronic kidney disease and cardiovascular disease and can lead to problems such as heart attacks, stroke, kidney failure, blindness, rupture of blood vessels and cognitive disorders (2)(3)(4). Hypertension is defined systolic blood pressure of 130 mm Hg or higher and diastolic blood pressure of 80 mm Hg or higher (5). Hypertension is also one of the preventable risk factors for disability and early mortality in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in recent years have reported the positive impact of using mobile capabilities on self-care in patients with hypertension (5,13). Some studies have also questioned the efficacy of using this technology in these patients (14).…”
Section: Introductionmentioning
confidence: 99%
“…The study interventions were selected due to strong evidence of effectiveness in resource‐constrained settings. One effective primary care intervention is nurse‐led adherence clubs, another is incorporating text‐messages into hypertension care (Khabala et al ; Zha et al ). Nurse‐led clubs studied in Kenya and South Africa judiciously used nurse time, expanded access to care and enhanced medication adherence (Khabala et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Nurse‐led clubs studied in Kenya and South Africa judiciously used nurse time, expanded access to care and enhanced medication adherence (Khabala et al ). Texting is a practical, low‐cost intervention that has enhanced adherence and improved outcomes in numerous clinical environments (Zha et al ). The practice intervention tested in this study was a bundle of monthly nurse‐led adherence clubs focusing on education with the addition of weekly text message reinforcement, referred to as the Bundled Education and Support with Text (BEST) intervention.…”
Section: Introductionmentioning
confidence: 99%